METAPHORICAL LANGUAGE IN “THE LORD OF THE RINGS AND THE FELLOWSHIP OF THE RINGS” MOVIE (A CONVERSATION ANALYSIS) - La Dunifa; La Ode Mutawakal (English Education Journal, 2022)
This study aimed to analyze the metaphors in the film “The Lord of The Rings and The Fellowship of The Rings” (LR & FR) and explained the metaphors structurally, orientationally, and ontologically. The problem studied in this paper is "How does the metaphor in the LR & FR film affect the messages conveyed in this film?" This research is a content analysis applies a qualitative approach in which the dialogue in the film as the source of data. The results of the study found that the metaphor in the LR & FR film expresses the origin domain to the target domain with a pattern that emphasizes meaning. The metaphorical concept of the source domain corresponds to the concept of the target domain. Metaphor in the film LR & FR as a figurative language has the same quality in representing a concept into a concept.